2010
DOI: 10.1007/s12010-010-8987-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mineral Ions on the Microbial Production and Molecular Weight of Hyaluronic Acid

Abstract: This study aimed to evaluate the influence of the culture medium supplementation with mineral ions, focusing on the growth of Streptococcus zooepidemicus as well as on the production and average molecular weight (MW) of hyaluronic acid (HA). The ions were investigated in terms of individual absence from the totally supplemented medium (C+) or individual presence in the non-supplemented medium (C-), where C+ and C- were used as controls. Differences between the effects were analyzed using the Tukey's test at p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Although sugarcane molasses generally contains essential nutrients beneficial to microorganism growth, it also has metal ions and suspended colloids, which may be detrimental to microorganisms because they influence the medium pH and inactivate enzymes associated with product biosynthesis [25]. The individual presence of Na + and Fe 2+ in medium containing glucose and yeast extract inhibited HA production by S. zooepidemicus ATCC 39920 [31]. Moreover, Tlapak-Simmons et al [32] reported that hyaluronan synthase was sensitive to the concentrations of monovalent cations such as Na + and K + .…”
Section: Effect Of Sugarcane Molasses Pretreatmentmentioning
confidence: 99%
“…Although sugarcane molasses generally contains essential nutrients beneficial to microorganism growth, it also has metal ions and suspended colloids, which may be detrimental to microorganisms because they influence the medium pH and inactivate enzymes associated with product biosynthesis [25]. The individual presence of Na + and Fe 2+ in medium containing glucose and yeast extract inhibited HA production by S. zooepidemicus ATCC 39920 [31]. Moreover, Tlapak-Simmons et al [32] reported that hyaluronan synthase was sensitive to the concentrations of monovalent cations such as Na + and K + .…”
Section: Effect Of Sugarcane Molasses Pretreatmentmentioning
confidence: 99%
“…Zhang et al developed a serum-free medium with starch as exclusive carbon source, and HA concentration reached 6.7 g/L [23]. The mineral ions and initial glucose concentration also had significant effects on microbial HA production [24,25]. The absence of glucose resulted in a mixed acid metabolism independent of the oxygen supply, while, for the initial glucose concentrations ranging from 5 to 90 g/L, the homolactic metabolism was prevalent [25].…”
Section: Introductionmentioning
confidence: 99%
“…The production in molasses was 51 % higher than that in glucose because this source is rich in fermentable sugars, amino acids and metallic ions (e.g., Fe 2+ ) that could improve hyaluronic acid production, as observed by Choi and co-workers [9]. Treatment with activated charcoal could result in a source with fewer inhibitors to hyaluronic acid production, such as inhibitor protons [35,40]. Pan et al [32] observed that pre-treated molasses yielded higher hyaluronic acid production than crude molasses.…”
Section: Optimization Of Hyaluronic Acid Productionmentioning
confidence: 93%